2018
DOI: 10.1101/399840
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Perceptual inference employs intrinsic alpha frequency to resolve perceptual ambiguity

Abstract: The brain uses its intrinsic dynamics to actively predict observed sensory inputs, especially under perceptual ambiguity. However, it remains unclear how this inference process is neurally implemented in biasing perception of ambiguous inputs towards the predicted percepts. Using electroencephalography and intracranial recordings, we first show that the alpha-band frequency defines a unified time window for perceptual grouping across both space and time: information segments, either spatially or temporally seg… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 97 publications
0
6
0
Order By: Relevance
“…At the neural level, oscillations in brain activity have long been speculated to be involved in discrete perceptual sampling. For instance, within‐ and between‐subject variation in alpha‐band frequency (7–14 Hz) is predictive of temporal properties of visual (Baumgarten et al, 2018; Coffin & Ganz, 1977; Coffin, 1977; Gray & Emmanouil, 2020; Gulbinaite et al, 2017; Kristofferson, 1967b; Minami & Amano, 2017; Ro, 2019; Samaha & Postle, 2015; Shen et al, 2019) and cross‐modal perception (Cecere et al, 2015; Cooke et al, 2019; Keil & Senkowski, 2017), with higher‐frequency oscillations being associated with finer‐grained temporal resolution. Moreover, the phase of ongoing alpha activity predicts perception of near‐threshold visual stimuli (Alexander et al, 2020; Busch et al, 2009; Dugué et al, 2011; Mathewson et al, 2009; Samaha et al, 2015; Samaha et al, 2017; Sherman et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…At the neural level, oscillations in brain activity have long been speculated to be involved in discrete perceptual sampling. For instance, within‐ and between‐subject variation in alpha‐band frequency (7–14 Hz) is predictive of temporal properties of visual (Baumgarten et al, 2018; Coffin & Ganz, 1977; Coffin, 1977; Gray & Emmanouil, 2020; Gulbinaite et al, 2017; Kristofferson, 1967b; Minami & Amano, 2017; Ro, 2019; Samaha & Postle, 2015; Shen et al, 2019) and cross‐modal perception (Cecere et al, 2015; Cooke et al, 2019; Keil & Senkowski, 2017), with higher‐frequency oscillations being associated with finer‐grained temporal resolution. Moreover, the phase of ongoing alpha activity predicts perception of near‐threshold visual stimuli (Alexander et al, 2020; Busch et al, 2009; Dugué et al, 2011; Mathewson et al, 2009; Samaha et al, 2015; Samaha et al, 2017; Sherman et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Importantly, in light of the increasing popularity of instantaneous frequency as a measure in EEG research (e.g. Babu Henry Samuel et al, 2018;Samaha & Postle, 2015;Shen et al, 2018;Wutz et al, 2018), our results caution against an interpretation of such effects in terms of genuine frequency shifts involving one oscillator, without controlling for the possibility of asymmetric power shifts over multiple oscillators.…”
Section: Increased Alpha Frequency Does Not Independently Predict Incmentioning
confidence: 56%
“…Whereas instantaneous alpha frequency reflects the timing of neuronal spiking and an oscillatory mechanism that is directly relevant to sensory perception (Cohen, 2014;Haegens et al, 2011;Klimesch et al, 2007;VanRullen, 2016), alpha desynchronization is directly relevant to memory encoding (Hanslmayr et al, 2016(Hanslmayr et al, , 2012. Thus, alpha frequency relates more to visual perception (Samaha and Postle, 2015;Shen et al, 2019;Wutz et al, 2018) than to visual memory performance. Indeed, we showed that alpha desynchronization, but not alpha frequency, was associated with individual differences in memory performance.…”
Section: Discussionmentioning
confidence: 99%
“…Electrophysiological evidence suggests that visual perception happens in a cyclic manner such that particular phases of the alpha cycle are associated with increased neural activity (Haegens et al, 2011;Klimesch et al, 2007) and thus more efficient sensory perception than others (Busch et al, 2009;Busch and VanRullen, 2010;Mathewson et al, 2009). Therefore, time-resolved peak alpha frequency, measured here by instantaneous frequency (Cohen, 2014), may index the temporal resolution of perception (Samaha and Postle, 2015;Shen et al, 2019;Wutz et al, 2018).…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation